Hubungan Manajemen Waktu dengan Kebiasaan Prokrastinasi Penyusunan Skripsi pada Mahasiswa Keperawatan - Arum Priharnadi; Samsualam; Mappangandro, Andi (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2022)
Students who practice the habit of procrastination take longer to complete their study period compared to students who do not procrastinate. Compiling a thesis is one of the important areas but this is often delayed by students. The purpose of this study is to find out whether there is a relationship between time management and the procrastination habit of thesis preparation in students of the nursing science study program of FKM UMI. The research design used is analitic pobservational with a cross sectional study approach. The sample determination was carried out using a total sampling technique with a sample size of 48 respondents. The relationship test was carried out using the Chi- Square statistical test with a meaningfulness level of p ≤ 0.05. The results showed that there was a relationship between time management and the procrastination habit of thesis preparation with a meaningfulness level of p ≤ 0.04. The conclusion of this study is the effective time management of nursing students of the Faculty of Public Health, Universitas Muslim Indonesia as many as 39 people (81.3%) and students who have ineffective time management as many as 9 people (18.7%), nursing students of the Faculty of Public Health, Muslim University of Indonesia who do not procrastinate as many as 40 people (83.3%), and those who carry out the habit of procrastination as many as 8 people (16.7%). It is necessary to conduct further research with other methods and more samples in order to get even more accurate results in the future.